Narrativas da América: o confronto com o desconhecido - Isotani, Mina (Estudos Japoneses, 2008)
Nagai Kafu s Amerika Monogatari is a book that contains twenty-three narratives written in the period from 1903 to 1907, time in that the writer lived in the United States. This work illustrates the author’s reflection on themes as the Japanese immigration at the beginning of the XX century, the encounter with the western culture and the Japanese society after the Meiji Revolution. In the present session of “Post Graduate Studies” it will be made one brief presentation of the results gotten during the period of research for the accomplishment of the dissertation entitled Narratives of America: The Confrontation with the Stranger.